How Training in Scholarly Writing by University Libraries Supports Postgraduate Research at University of Embu and Kenya Methodist University in Kenya - Maina, Antony Mwangi; Gichohi, Paul Maku; Nzioka, Catherine Mueni (International Journal of Professional Practice, 2023)
Academic dishonesty is a significant challenge facing postgraduate research in universities. While this challenge persists, students across the globe continue to enrol in postgraduate studies. Universities employ various measures to mitigate academic dishonesty, including using antiplagiarism software, creating academic dishonesty awareness, and training students on scholarly writing. However, academic dishonesty continues to persist in postgraduate research, lowering research quality. The current study sought to investigate how training scholarly writing supports postgraduate research at the University of Embu (UoEM) and Kenya Methodist University (KeMU) in Kenya. The research used a survey research design. The target population was 1008 participants, consisting of postgraduate students, Directors of Postgraduate Studies, and librarians. Using Mugenda and Mugenda (2003) formula, the study used a sample size of 208 participants, including 195 postgraduate students, two directors of postgraduate studies, and 11 librarians. The research used stratified random sampling to establish the research sample and simple random sampling within each population stratum. Interviews and questionnaires were used to collect data from the respondents. Descriptive statistics and thematic analysis were used to analyse research data. The study established that training in scholarly writing is an effective approach in mitigating academic dishonesty. The findings indicated that postgraduate research is vital in academics. Therefore, the use of scholarly writing training as a mitigation measure against academic dishonesty among postgraduate students is necessary. The training approaches used by many universities to introduce postgraduate students to scholarly writing concepts include practical training and orientation of new students. The research recommended inclusion of training in scholarly writing to the curriculum. Further, it recommended collaboration of all stakeholders to identify areas that need more emphasis and training, and to incorporate social media platforms and student university portals in the training.